2010
DOI: 10.1037/a0019932
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic roots of cognitive dissonance.

Abstract: Egan, Santos, and Bloom (2007). In experimental trials, subjects were given choices between 2 equally preferred food items and then presented with the unchosen option and a novel, equally preferred food item. In control trials, subjects were presented with 1 accessible and 1 inaccessible option from another triad of equally preferred food items. They were then presented with the previously inaccessible item and a novel member of that triad. Subjects, as a whole, did not prefer the novel item in experimental or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…As emphasized earlier [10], this likely results from choice-induced preference, a cognitive bias shared by humans [43], [44] and monkeys, whether capuchins [45], [46], or macaques [47]. Subjects value an option more when they select it, regardless of its outcome.…”
Section: Discussionmentioning
confidence: 88%
“…As emphasized earlier [10], this likely results from choice-induced preference, a cognitive bias shared by humans [43], [44] and monkeys, whether capuchins [45], [46], or macaques [47]. Subjects value an option more when they select it, regardless of its outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Despite merely having the illusion of choice, capuchins still showed the same choice-induced preference changes, which suggests that preexisting preferences between the two options could not account for the monkeys’ performance (for a discussion of this alternative explanation, see Chen & Risen 2009). In addition, West and colleagues (2010) demonstrated that these choice-induced preference changes may be specific to primate psychology: Although West and colleagues replicated the basic preference change effect with several different primate species, they found no such choice-induced shifts in several other nonprimate mammal and bird species. Taken together, these findings of choice-induced preference changes in primates provide important hints about the mechanisms that may underlie these preference changes in humans.…”
Section: Do Humans Have Unique Mechanisms For Decision Making?mentioning
confidence: 99%
“…The original paper describing the methodological flaw was made available to the public as a working paper in 2008 and attracted the attention of researchers (see Chen and Risen, 2009; Sagarin and Skowronski, 2009a,b). However, despite the fact that their critique could potentially undermine the conclusions of any study that uses the paradigm, behavioral, and neuroimaging studies using the paradigm continue to be published without addressing the critique (Sharot et al, 2009, 2010a; Coppin et al, 2010, 2012; Imada and Kitayama, 2010; Lee and Schwarz, 2010; West et al, 2010; Harmon-Jones et al, 2011; Jarcho et al, 2011; Qin et al, 2011; Kimel et al, 2012; Kitayama et al, 2013). Furthermore, although some researchers have already provided evidence for the existence of choice-included preference change using new paradigms or modifications of the free-choice paradigm, some of them are not sufficiently compelling, as detailed later.…”
Section: Introductionmentioning
confidence: 99%